2000
DOI: 10.2307/420868
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Service Learning on Democratic and Civic Values

Abstract: Throughout the twentieth century, American scholars and political pundits have argued that the survival of democratic political institutions and an ethic of concern for the welfare of others in the political community depended on ensuring all citizens received a high-quality civic education. Despite repeated efforts to act on this concern, empirical evidence suggests that a substantial number of Americans continue to be ignorant of how best to express their political demands, lack essential factual knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…Service-learning courses (also known as community-based learning or experiential learning) ask students to perform public-spirited work as an integral and integrated part of the course curriculum (for a review of this literature, see Eyler et al 2001). Proponents claim service-learning courses offer a number of benefits, not least of which is the development of students' civic skills (Astin and Sax 1998;Astin et al 2000;Ehrlich 1999;Metz and Youniss 2003;Yates and Youniss 1998; for an opposite view, see Hunter and Brisbin 2000). Critics, however, counter that service-learning courses are akin to "compulsory volunteering" in which students perform community service simply to fulfill a course requirement, gaining little out of the experience beyond a grade (Butin 2005;Fish 2003;Sobus 1995;Stukas et al 1999).…”
mentioning
confidence: 99%
“…Service-learning courses (also known as community-based learning or experiential learning) ask students to perform public-spirited work as an integral and integrated part of the course curriculum (for a review of this literature, see Eyler et al 2001). Proponents claim service-learning courses offer a number of benefits, not least of which is the development of students' civic skills (Astin and Sax 1998;Astin et al 2000;Ehrlich 1999;Metz and Youniss 2003;Yates and Youniss 1998; for an opposite view, see Hunter and Brisbin 2000). Critics, however, counter that service-learning courses are akin to "compulsory volunteering" in which students perform community service simply to fulfill a course requirement, gaining little out of the experience beyond a grade (Butin 2005;Fish 2003;Sobus 1995;Stukas et al 1999).…”
mentioning
confidence: 99%
“…For service and service-learning, studies have found robust effects on personal and civic development, such as increased tolerance and understanding; spiritual and social growth; sense of personal efficacy; and commitment to public service, engaged citizenship, and social justice (Warchal and Ruiz 2004;Hunter and Brisbin 2000;Astin, Sax, and Avalos 1999;Eyler and Giles 1999;Gray et al 1998;Osborne, Hammerich, and Hensley 1998;Giles and Eyler 1994;Markus, Howard and King 1993). Studies also have found that service-learning enhances students' educational experience, for example, by helping them to understand social problems in all their dimensions, apply academic theory to real-world contexts, sharpen critical-thinking and problem-solving skills, and deepen their understanding of concepts learned in the classroom (Eyler and Giles 1999;Osborne, Hammerich, and Hensley 1998;Batchelder and Root 1994;Boss 1994;Markus, Howard, and King 1993).…”
Section: Rsl's Place In Service-learning and Community-based Researchmentioning
confidence: 99%
“…At the end of the planning process, the university hopes that, as a result of working with the communities in Harrison County, the students will have positive attitudes toward their own communities, greater involvement in politics, and instilled values of citizenship (Ahmad-Llewellyn, 2003;Hunter and Brisbin, 2000;Kirlin, 2002). In reviewing the students' journals, instructors found that their attitudes toward citizen engagement had clearly changed.…”
Section: Citizen Engagement In Post-hurricane Katrina Planning In Harmentioning
confidence: 99%